Physicochemical Properties of Poly-vinyl Polymers and Their Influence on Ketoprofen Amorphous Solid Dispersion Performance: A Polymer Selection Case Study - Emer Browne; Zelalem A. Worku; Anne Marie Healy (MDPI AG, 2020)
When developing an amorphous solid dispersion (ASD), a prudent choice of polymer is critical to several aspects of ASD performance including: processability, solid state stability and dissolution rate. However, there is little guidance available to formulators to aid judicious polymer selection and a "trial and error" approach is often taken. This study aims to facilitate rational polymer selection and formulation design by generating ASDs using a range of poly-vinyl polymers and ketoprofen as a model active pharmaceutical ingredient (API) and evaluating several aspects of their performance. The molecular weight of the polymer and the ratio of vinyl pyrrolidone to vinyl acetate in the polymer were found to influence the relative humidity at which the relative humidity induced glass transition occurred, as well as the extent of ketoprofen supersaturation achieved during dynamic solubility testing. Interestingly, ASD tablets containing polymers with the vinyl pyrrolidone functional group exhibited higher tensile strengths than those without. This points towards the binder functionality of vinyl pyrrolidone. In conclusion, the physicochemical properties of poly-vinyl polymers greatly influence ketoprofen ASD performance and due regard should be paid to these properties in order to develop an ASD with the desired attributes.